(untitled) (Physical Culture and Sport: Scientific Perspective, 2022)
The article deals with theoretical and experimental research of the issue of formation of motivation to self-improvement of teachers of physical education in the process of professional activity. The aim of research is to analyze motivation to self-improvement of teachers of physical education in the process of professional activity. A number of methods have been used: analysis, comparison, systematization, observation, discussion, teachers interviewing, questioning, pedagogical experiment, methods of mathematical statistics and graphic display of the results of research. Study of motivation to self-improvement of teachers of physical education in the process of their professional activity was based on primary sources of motivation as fundamental personal formations mentioned by J. Barbuto and R. Scholl in their works. Five sources of motivation have been pointed out: inner processes; instrumental motivation; external self-concept, internal self-concept; aim internalization. Motivational structure of each teacher of physical education can have all sources of motivation; however, expressiveness of each of them in a motivational profile interested us the most. We assume that motivation leads and organizes teachers’ activity, provides personal essence and significance of self-improvement under conditions of professional activity, promotes transformation of externally-formulated aims into inner needs. Basic trends of an effective influence on intensification of motivation to self-improvement of teachers were as follows: formation of positive guideline for self-improvement in the process of professional activity with the help of specification of requirements to specialists; formation of solid knowledge and skills that are a significant factor for development of motivation to professional self-improvement and personal development; actualization of the need in professional growth. Primary actions regarding intensification of motivation of teachers of physical education to self-improvement in the process of professional activity included administering scientific and methodological seminars, trainings related to professional growth. Given the available researches of motivational processes, we made a conclusion that intrinsic motivation is very important for self-improvement of teachers of physical education in the process of their professional activity. The results of research show that intrinsic motives dominate with the majority of teachers from the experimental group, which highlights positive attitude to pedagogical activity and intensified motivation to self-improvement in the process of professional activity.